La nuptialité dans le Sud marocain. Évolution des mœurs ou contraintes économiques ? - Leila Boufraioua (Les Cahiers d’EMAM)
In Morocco, since the late twentieth century, the marriage pattern has undergone profound changes. Within a few decades, early marriage has shifted toward late one and mate selection which was previously belonged to the authority of elders almost exclusively is gradually replaced by greater freedom of younger generations. To carry out this study on the marriage it was necessary to conduct a survey in southern Morocco, especially in the region of Sidi Ifni, where marriage greatly evolved between tradition and modernity. We focused our study on men and women aged 15 to 35 years residing in Sidi Ifni, regardless of their marital status. Does the delay in first marriage of male and female depend on the same explanatory variables? We will examine the degree of similarity or dissimilarity between the patterns of first marriage for men and women and the factors behind this delay.